Annual assembly of delegates, held at [...] London, May 28th to June 2nd, 1923, May 26th to June 5th, 1924, May 18th to May 22nd, 1925, [and] June 28th to July 3rd, 1926 (Twentieth Century Press)
The Associated Society of Locomotive Engineers and Firemen.